Identification of the Bisphenol A (BPA) and the Two Analogues BPS and BPF in Cryptorchidism - Komarowska, Marta Diana; Grubczak, Kamil; Czerniecki, Jan; Hermanowicz, Adam; Hermanowicz, Justyna Magdalena; Debek, Wojciech; Matuszczak, Ewa (Frontiers in Endocrinology, 2021)
Objective: to explore the association of plasma concentrations of bisphenol A (BPA), bisphenol S (BPS), and bisphenol F (BPF) with unilateral cryptorchidism. In addition, to analyze selected demographic and intraoperative characteristics. Design: Retrospective analysis to determine plasma concentrations of total BPA, BPS and BPF using gas chromatography - mass spectrometry (GC-MS) among prepubertal boys with cryptorchidism and prebupertal male control subjects. During operation, the size, turgor and location of the cryptorchid testes were assessed. Main outcome measure: Plasma concentrations of total BPA, BPS and BPF. Results: In children with cryptorchidism, plasma levels of BPA, BPS and BPF were significantly higher compared to the control subjects. For BPA, it was: median value: 9.95 ng/mL vs. 5.54 ng/mL , p<0.05. For BPS, it was: median value: 3.93 ng/mL vs. 1.45 ng/mL, p<0.001. For BPF, it was: median value: 3.56 ng/mL vs. 1.83 ng/mL , p<0.05. In cryptorchid group, BPA was detected in 61.4% samples, BPS in 19.3% and BPF in 19.3%. All the three bisphenols were detected in plasma samples of both the healthy subjects and the study cohort. In the latter group, we found significant higher levels of BPA in boys from urban areas. We found a weak positive correlation between the levels of BPS and BPF and reduced turgor of the testes. Furthermore, results showed weak positive correlations between BPA and BPS levels and the age of the children as well as between BPS and BPF concentrations and the place of residence. Conclusions: Results provide a first characterization of prepubertal boys suffering from cryptorchidism and exposed to different kind of bisphenols. Our study suggests that cryptorchid boys are widely exposed to BPA and, to a lesser extent, also to its alternatives, such as BPS and BPF.